Relativização atípica da coisa jugada à luz da segurança jurídica - Celestino, Luis Felipe dos Santos (2025)
Res judicata, a fundamental institution in the legal system, aims to ensure legal certainty and stability in social relations, definitively ending litigation on a given matter. However, the possibility of relativizing res judicata in cases of unjust decisions has sparked intense doctrinal and jurisprudential debate. This work investigates the admissibility of atypical relativization of res judicata, that is, its annulment in situations not provided for by law, at any time, considering the tension between the pursuit of justice and the need to preserve legal certainty. Thus, it aims to analyze the feasibility of atypical relativization in the Brazilian civil procedural legal system, in light of legal certainty and the pursuit of justice. To this end, the research conceptualizes res judicata and its limits, analyzes the concept of atypical relativization, examines the importance of legal certainty, assesses the tension between justice and legal certainty, and investigates the arguments for and against relativization. The methodology used is bibliographic research, exploring doctrine, legislation, and jurisprudence on the topic. The research reveals that atypical relativization, although it may seem like a solution to correct injustices, poses a serious threat to legal certainty. Allowing the relativization of res judicata in an atypical manner, without express legal provision, would create legal uncertainty and undermine the effectiveness of the judicial system. It is concluded, therefore, that res judicata should not be relativized atypically, as it violates legal certainty, a fundamental principle of the Democratic Rule of Law. The pursuit of justice must be achieved through means compatible with legal certainty, such as the use of legal remedies and the filing of rescissory actions in the hypotheses expressly provided for in the Code of Civil Procedure. The possibility of legislative changes to provide for specific hypotheses of relativization of res judicata, respecting strict and exceptional criteria, could be an alternative to reconcile the pursuit of justice with the preservation of legal certainty.